Latent Membrane Protein 1 Gene of Epstein - Barr virus: 30-Base-Pair Deletion in Indonesian Nasopharyngeal Carcinoma Patients - Yurnadi Hanafi Midoen (Journal of Global Pharma Technology, 2020)
Introduction: Epstein Barr Virus (EBV), a member of the Herpesviridae family, is a dsDNA virus. Nasopharyngeal carcinoma (NPC) patients express EBV latent genes EBERs, EBNA1, LMP1, LMP2A, and LMP2B. The LMP1 gene, in particular, plays important roles in epithelial oncogenesis and B-lymphocyte transformation. Several epidemiological studies found a specific variant of LMP gene detectable as a 30-bpdeletion in NPC patients and it is still unclear whether this deletion is associated with NPC pathogenesis in Indonesian population. The aim of this research is to understand the existence of the deletion of the 30-bp LMP1 gene in Indonesian NPC patients and to determine the frequency of 30-bp deletion of LMP1 gene and its association with the pathological status. Methods: The 30-bp deletion in LMP1 gene was identified by nested PCR and subsequent electrophoresis in 2% agarose gel. The results were determined as 162-bp DNA band of the LMP1 gene (without 30-bp deletion) and 132-bp DNA band of the LMP1 gene (with 30-bp deletion). Results: Among 100 identified samples from Jakarta, 8 samples were found to have the 30-bp deletion, 71 samples did not have 30-bp deletion and 21 samples carried coexistence variants. Conclusion: In Indonesia, especially in Jakarta, EBV variant of 30-bp deletion of LMP1 gene was found at low frequency (8%) in comparison with variant without deletion (71%). There is a variant of LMP1 gene mixtures (21% coexistence with and without deletion). Analysis of data using Fisher's exact test shows that there is no significant relationship between 30-bp deletion of LMP1 gene and NPC pathological status (p> 0.05).Key words: 30-bp deletion, NPC, EBV, LMP1, Coexistence